Expression, subunit composition, and function of AMPA‐type glutamate receptors are changed in activated microglia; possible contribution of GluA2 (GluR‐B)‐deficiency under pathological conditions. Issue 6 (7th March 2013) - Beppu, Kaoru; Kosai, Yuki; Kido, Mizuho A.; Akimoto, Nozomi; Mori, Yuki; Kojima, Yuichiro; Fujita, Kyota; Okuno, Yuko; Yamakawa, Yukiko; Ifuku, Masataka; Shinagawa, Rika; Nabekura, Junichi; et al.
<x xml:space="preserve">Abstract</x> Microglia express AMPA (α‐amino‐hydroxy‐5‐methyl‐isoxazole‐4‐propionate)‐type of glutamate (Glu) receptors (AMPAR), which are highly Ca2+ impermeable due to the expression of GluA2. However, the functional importance of AMPAR in microglia remains to be investigated, especially under pathological conditions. As low expression of GluA2 was reported in some neurodegenerative diseases, GluA2−/− mice were used to show the functional change of microglial AMPARs in response to Glu or kainate (KA). Here we found that Glu‐induced currents in the presence of 100 μM cyclothiazide, an inhibitor of AMPAR desensitization, showed time‐dependent decrease after activation of microglia with lipopolysaccharide (LPS) in GluA2+/+ microglia, but not in GluA2−/− microglia. Upon activation of microglia, expression level of GluA2 subunits significantly increased, while expression of GluA1, A3 and A4 subunits on membrane surface significantly decreased. These results suggest that nearly homomeric GluA2 subunits were the main reason for low conductance of AMPAR in activated microglia. Increased expression of GluA2 in microglia was also detected partially in brain slices from LPS‐injected mice. Cultured microglia from GluA2−/− mice showed higher Ca2+‐permeability, consequently inducing significant increase in the release of proinflammatory cytokine, such as TNF‐α. The conditioning medium from KA‐treated GluA2−/− microglia had more neurotoxic effect on wild type cultured neurons than that from KA‐treated GluA2+/+ microglia. These results suggest that membrane translocation of GluA2‐containing AMPARs in activated microglia has functional importance and thus, dysfunction or decreased expression of GluA2 may accelerate Glu neurotoxicity via excess release of proinflammatory cytokines from microglia.